Memahami Konsep Pengajuan Lelang Untuk Jasa Konsultan Konstruksi Pada Proses Pengadaan Barang/Jasa - Meylida, Dhonna; Hidayawan, Ahmad; Setiyanto, Beni (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
In the construction sector, the tender process in the procurement of goods and services is carried out to select and appoint companies that will perform the required work. Companies that feel capable may participate in tender offers, and the selected company will carry out the work in accordance with the agreed contract. The procurement of goods and services, also known as tendering, is a government procedure aimed at awarding projects to entrepreneurs. Government procurement is conducted through an e-procurement or electronic tender process, in accordance with Presidential Regulation No. 04 of 2015. This process is intended to minimize direct meetings between the organizing committee and service providers, thereby promoting fair competition. The electronic tender process includes steps such as the announcement of the tender, downloading of selection and qualification documents, clarification of tender documents, submission of bid documents (price, administrative, and technical), submission of qualification documents, evaluation of bids, evaluation of qualification documents and verification of qualifications, delivery of the minutes of tender results, determination of the winner, announcement of the winner, objection period for the tender result, and signing of the contract. This paper uses a literature review method by analyzing several articles, journals, books, and official circulars relevant to the author's objective, which is to understand the procurement process for goods and services in construction consultancy. From the results of the literature review, it is found that there are many steps required to achieve optimal outcomes in the tender process for goods and service providers. Due to various regulatory changes, it is important for providers to study applicable rules, such as the latest Presidential Regulation No. 1 of 2025 regarding budget efficiency in construction. Providers are thus required to prepare pricing that matches the project specifications being tendered, while also staying within existing efficiency limits. This paper is expected to assist small or newly established companies in participating in fair and healthy competition. It is important to consider the company’s capacity to participate in tenders, as well as compliance with current regulations, including proper calculation of the Domestic Component Level (TKDN).